Avaliação institucional interna na Educação Profissional Técnica de Nível Médio: instrumento de melhoria do ensino - Borges, Nieysila Simara da Silva Castro (2019)
The internal institutional evaluation constitutes a relevant process for the institutions to analyze them practices, to learn about themselves, to identify potentialities and fragilities and to improve them pedagogica l project. The research is part of the Management and Organization of Pedagogical Spaces in Professional and Technological Education and aimed to build a proposal for an internal institutional evaluation for the medium level technical professional educati on (EPTNM) courses at the IFMA Campus Grajaú, to improve of teaching practices and the strengthening of integral human formation. Duri ng the methodological course, had adopted the qualitative approach, participant research as a method and the technique of conversation group . Representatives of the teaching, student, techni cal administrative and parent/ guardian segments participated in the talks. The conversational group intended to discuss theoretical and methodological elements for the structuring of a p roposal of internal institutional evaluation that meets the specificities of the technical courses of average level. The study made possible the understanding of the need of the participation of the actors of the school and systematized theoretical contrib ution to support the internal institutional evaluation in the EPTNM courses. The educational product developed in the research indicated theoretical and methodological orientations for the implementation of the internal institutional evaluation for the cou rses of EP TNM with intent to the institutional self knowledge and the improvem ent of the teaching. It is hope that the proposal will allow a process, participative and formative, analysis of the practices and provide important subsidies for the decision ma king around the improvement of teaching, in the scope of professional and technological education.